(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Reusing medical instruments in care and treatment at medical examination and treatment facilities is a routine practice. This reuse process, if not strictly followed from cleaning to disinfection and sterilization, can have serious consequences, affecting the quality of examination and treatment of patients. Objectives: Describe the knowledge and practice on disinfection, sterilization medical instruments of medical staff at the National Eye Hospital and analyze some related factors. Methods: Cross-sectional survey, quantitative research. Results: This study collected information from 323 health workers (NVYT), National Eye Hospital through questionnaires and observation using checklists. The research results show that the knowledge and practice on disinfection, sterilization medical instruments in the control of hospital-acquired infections of health workers is quite good. Conclusion: The rate of health workers with knowledge on disinfection, sterilization medical instruments reached 67,2%. The rate of health workers with practices on on disinfection, sterilization medical instruments reached over 80%. There are 4 factors related to knowledge on disinfection, sterilization medical instruments including: age, working position, working time and professional qualifications. Three factors related to practices on disinfection, sterilization medical instruments including: Gender, working position and time of training on infection control (p<0.05).